Macroeconomics for management students - "Nag, A." (Delhi, 2005)
Acquaints management students with the macroeconomic framework that provides the general economic environment within which business decisions are taken. This has been designed as an induction level textbook and can be used by both BBA and MBA students for a foundation course in macroeconomics. This second edition of the book is a restructured, enlarged, revised and updated edition.
Keywords: Macroeconomics